Follow-up analysis of blood vessel regeneration in young permanent teeth of patients with pulp necrosis using platelet-rich fibrin - Maibubaimu MAIMAITIYIMING, Mayinuer AISAITI, Pawuziye PAERHATI, Riziwaguli AMUTI (Kouqiang yixue)
Objective To explore the therapeutic effect of injectable plateletrich fibrin(i-PRF) as a scaffold for pulp regeneration surgery in young permanent teeth with pulp necrosis. Methods Sixty young children with permanent tooth pulp necrosis who underwent pulp regeneration surgery in the Department of Stomatology of our hospital from March 2021 to October 2022 were included. The differentiation between the i-PRF group(33 cases)and the blood clot group(27 cases) was based on the different scaffold materials used during the treatment process. Follow up for 1 year, cone beam CT(CBCT) was used to measure the apical foramen diameter, dentin wall thickness, root length, root canal area, and root area of the affected tooth before treatment, at 3, 6, 9 and 12 months of treatment. The increase in root length, increase in dentin wall thickness, decrease in apical foramen diameter, increase in root area, decrease in root canal area, and clinical data between the two groups of patients before and after treatment were compared. The tooth color, pulp vitality, and tooth eruption height of two groups of patients were recorded before and after treatment. Results At 9 and 12 months post surgery follow-up, the root length, dentin wall thickness, and root area of the i-PRF group were higher than those of the blood clot group(P<0.05). According to the results of the last follow-up, it was calculated that the increase in root length, dentin wall thickness, and root area in the i-PRF group were higher than those in the blood clot group, and the differences were statistically significant(P<0.05). There was no statistically significant difference in the changes in tooth color, positive pulp vitality, and eruption height between the two groups of patients(P>0.05). Conclusion The use of blood clots and i-PRF as scaffolds for pulp regeneration in the treatment of young permanent tooth pulp necrosis has been proven to be effective, but the use of i-PRF as a scaffold is more effective in promoting root growth and increasing dentin wall thickness.